Application of a Mass Balance Partitioning Model of Ra-226, Pb-210 and Po-210 to Freshwater Lakes and Streams - Britton, Kevin John (Université d'Ottawa / University of Ottawa, 2018)
The objectives of this thesis were: (1) to develop a mass balance partitioning model of the natural uranium-238 series comprising radium-226, lead-210 and polonium-210 and (2) to apply the model to estimate the source and fate of these radionuclides in freshwater lakes and streams. Samples were collected from Ottawa River watershed tributaries and measured for lead-210 and polonium-210 content to determine the water concentrations that were input to the model. The radium-226 partitioning model was developed by reconstructing and analyzing Quantitative Water, Air, Sediment Interaction (QWASI) models of lead for Lake Ontario and Hamilton Harbour and selecting parameters for an updated QWASI model of lead for a Lake Ontario basin. This study gave insight about model basis definition, and partition coefficient and sediment particle constraint. The radium-226 series model was formulated by connecting separate QWASI modules for radium-226, lead-210 and polonium-210 with decay and ingrowth terms. The radium-226 model was applied to studies of Crystal Lake, Wisconsin; Bickford Pond, Massachusetts; and Clinton River, Michigan, using parameters reported in these and other studies. Model error was evident in the applications to Crystal Lake due to underlying lake heterogeneity, to Bickford Pond due to unidentified sources of lead-210 from sediment diffusion or watershed runoff, and to Clinton River from watershed runoff. The model was applied to seven Laurentian Shield lakes in the Ottawa River watershed using the sample measurements as the basis for water concentration inputs. The application showed that hydrologic flushing rate may be a factor in the proportion of watershed atmospheric deposition and overall Pb-210 input to the water. Laurentian Shield Lakes with the lowest hydrologic flushing rates (<3 a-1) had proportions of Pb-210 losses to sediment greater than 85%. In another application to Judge Sissons Lake, Nunavut, the model indicated that the watershed was the source of about 85% of Pb-210 and 98% of Po-210 input to the water, and that a significant geologic component of Pb-210 input to the lake was likely. The model indicated that most of the Pb-210 in Judge Sissons Lake was lost to outflow, and that most of the Po-210 was lost to sediment. The model showed that sedimentation is a better proxy measurement for atmospheric deposition of Pb-210 to the Laurentian lakes than originally estimated. The model also showed that watershed contributions to Judge Sissons Lake could explain the observed background concentrations of Pb-210 and Po-210.